1999
DOI: 10.1590/s0034-71081999000100022
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos biológicos do camarão-espinho Exhippolysmata oplophoroides (Holthuis, 1948) (Crustacea, Caridea, Hippolytidae)

Abstract: O número de ovos e a taxa na qual eles são produzidos podem fornecer uma indicação do potencial reprodutivo de uma espécie. O objetivo deste estudo foi levantar dados básicos sobre a biologia geral de E. oplophoroides e, em particular, sua fecundidade na região de Ubatuba, SP. Os espécimes foram coletados em arrastos camaroneiros na Enseada de Ubatuba, SP (23ºS/45ºN), no período de junho/1995 a maio/1996. O número de ovos relacionados a uma dimensão corpórea (comprimento cefalotorácico) foi ajustado a uma regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
8
0
3
Order By: Relevance
“…Assuming that female size is closely linked to reproductive strategies (Hines, 1982), the positive relationship between CL and number of embryos Reproductive strategy of N. schmitti Nauplius, 25: 2017003 observed in N. schmitti is corroborated by previous studies of other caridean shrimps, such as Pandalus borealis (Clarke et al, 1991), Hippolyte zostericola (S. I. Smith, 1873) (Negreiros- Fransozo et al, 1996), Austropandalus grayi (Cunningham, 1871) (Wehrtmann and Lardies, 1999), Exhippolysmata oplophoroides (Holthuis, 1948) (Chacur and Negreiros-Fransozo, 1999), Hippolyte obliquimanus Dana, 1852 (Mantelatto et al, 1999) and Palaemon gravieri (Yu, 1930) (Kim and Hong, 2004). This positive relationship suggests that larger females produce more embryos because they have more energy resources and the ability to use it (Baeza, 2006), as well as more space in the abdomen to accommodate them (Clarke, 1993;Chacur and Negreiros-Fransozo, 1999;Mantelatto et al, 1999). In this study, we also observed that smaller females produce fewer embryos than larger females.…”
Section: Discussionsupporting
confidence: 67%
“…Assuming that female size is closely linked to reproductive strategies (Hines, 1982), the positive relationship between CL and number of embryos Reproductive strategy of N. schmitti Nauplius, 25: 2017003 observed in N. schmitti is corroborated by previous studies of other caridean shrimps, such as Pandalus borealis (Clarke et al, 1991), Hippolyte zostericola (S. I. Smith, 1873) (Negreiros- Fransozo et al, 1996), Austropandalus grayi (Cunningham, 1871) (Wehrtmann and Lardies, 1999), Exhippolysmata oplophoroides (Holthuis, 1948) (Chacur and Negreiros-Fransozo, 1999), Hippolyte obliquimanus Dana, 1852 (Mantelatto et al, 1999) and Palaemon gravieri (Yu, 1930) (Kim and Hong, 2004). This positive relationship suggests that larger females produce more embryos because they have more energy resources and the ability to use it (Baeza, 2006), as well as more space in the abdomen to accommodate them (Clarke, 1993;Chacur and Negreiros-Fransozo, 1999;Mantelatto et al, 1999). In this study, we also observed that smaller females produce fewer embryos than larger females.…”
Section: Discussionsupporting
confidence: 67%
“…According to Vogt (2012), this difference may be related to hormones and reproductive cost, but the mechanism for this difference is still not well understood. The greater longevity of females is a way to produce more eggs (Chacur & Negreiros-Fransozo, 1998), guaranteeing a more efficient stock replacement of the population. As observed in this study, it is common for males to have higher growth coefficient (k) and lower asymptotic growth compared with females (Gulland & Rothschild, 1981; Petriella & Boschi, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Both presence of sperm (testicular part) and ova (ovarian part) in ovigerous females shows synchronous hermaphroditism, ruling out the case of protandry. Chacur & Negreiros-Fransozo (1999) collected Exhippolysmata oplophoroides (Holthuis, 1948) from the Ubatuba, São Paulo, Brazil coastline and did not find any males in their samples, which led them to believe that this is a protandrous species. Fransozo et al (2005) also studied E. oplophoroides population biology in Ubatuba.…”
Section: Introductionmentioning
confidence: 99%